Pattern of Adverse Drug Reactions in a Govt. District Headquarters Hospital in Tamilnadu, India - Sivasankaran, Ponnusankar; Gupta, Megha; Satyanarayan, Roopa Basutkar; Durai, Raja (Indian Journal of Pharmacy Practice)
Background: Several literatures have reported adverse drug reaction between 5.9 to 22.3% among hospitalized patient in India and western countries respectively. The present study was undertaken to know the incidence of adverse drug reactions among the hospitalised patients at a secondary care hospital in South India. Method: One year and ten months prospective study included 1000 hospitalized patients at a secondary care hospital whose medical records were reviewed. Suspected adverse drug reactions were evaluated for causality, preventability and severity by Naranjo’s probability scale, modified Schumock and Thornton’s criteria, and modified Hartwig’s criteria, respectively. Results: Among the 1000 hospitalized patients medical charts reviewed, 80 patients experienced adverse drug reaction. Type A reaction accounted for most of adverse drug reaction. 73.75% of the adverse drug reaction was preventable. 56.25% was found to be mild, 43.75% moderate and none of adverse drug reactions was severe. Among the adverse drug reaction 43.75% were reported with diuretic class of drug. The organ systems affected mostly were gastro intestinal tract (46.25%) and haematological system (15%). The significant association was found with age and incidence of adverse drug reaction in the study population. The occurrence of ADR was higher in male medical and lesser in paediatric units. Conclusion: In the present study fewer hospitalised patients experienced adverse drug reactions than compared to study reported by western countries.
Keywords: Adverse drug reaction; Hospitalised patients; Pharmacovigilance; Medical units; Spontaneous reporting; South India